IMPLEMENTASI DAN EVALUASI SISTEM KEUANGAN DESA (SISKEUDES) DI PROVINSI JAWA TIMUR - Nur Khasanatun Nafi’ah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to measure the implementation of Rural Financial System (SISKEUDES) in East Java from the perspective of Finance and Development Supervisory Agency (BPKP) as the system developer and village government officials as users and to evaluate the implementation of the system. The data of this qualitative descriptive research were obtained from interviews on six informants, in which three of them are from BPKP and the other three are heads of village. The results show that the system is used by BPKP as a tool to realize accountability in accordance with its function. The main difficulty faced by village in implementing the system is related to the village government’s human resources. Age, educational background, and adaptation process are the factors of the difficulty. Therefore, synergy between human resources from BPKP and the village government is essential in the success of the system implementation, so the expected accountability can be achieved. Sustainable assistance from BPKP for village government officials is necessary to ensure that the officials have a sufficient competence in the implementation.Keywords: Accountability, Evaluation, Human Resources, SISKEUDES PENDAHULUAN